The Roman Principate and the political corruption: the ’repetundae’ trials in the Epistles of Pliny the Younger - Souza, Dominique Monge Rodrigues de (Romanitas - Revista de Estudos Grecolatinos, 2016)
The disadvantages of a bad government and the fight against corrupt practices have been debated since antiquity. In Rome, especially after the Second Punic War (218-201 B.C.), several measures were employed to contain the spread of the practices that were considered corrupt. One of them was to create laws to prevent and punish the poor provincial administration and the extortion committed by Roman magistrates, such as Lex Iulia repetundarum (59 BC). During the Principate, the search for ways to combat corruption continued. Therefore, this article aims to interpret the reports contained in the Epistles of Pliny the Younger concerning five repetundae trials against former governors of Roman provinces before senatorial court. Our study aims to understand the strategies employed in Rome to combat political corruption and the role of the Senate, as a court of justice, in the maintenance of the Empire administration.